Dynamical Forces Inside Facet Joints, Intervertebral Discs and Ligaments of Human Cervical Spine - M. Gzik; D. Tejszerska (Engineering Transactions)
The paper presents a dynamic spatial mathematical model in which a head, seven cendcal vertebrae, a group of 19 couples of neck muscles, 6 intervertebral discs, ligaments and facet joints are taken into consideration. The created model enables simulation of dynamical forces inside anatomical parts of human neck. The behaviour of the modelled body exposed to action of a force corresponding to the real enforcement, which occurs at a head-on collision during the road accident was simulated, and the model was verified on the basis of the data obtained from published experiments.